Solar Hydrogen Production Coupled with the Degradation of a Dye Pollutant Using TiO2 Modified with Platinum and Nafion - Jungwon Kim; Yiseul Park; Hyunwoong Park (International Journal of Photoenergy)
The simultaneous production of molecular hydrogen (H2) and degradation of rhodamine B (RhB) was successfully achieved using TiO2 modified with platinum and nafion (Pt/TiO2/Nf) under visible light (λ>420 nm). Pt/TiO2/Nf exhibited high activity for H2 production in the presence of RhB and EDTA as a photosensitizer (also an organic dye pollutant) and an electron donor, respectively. However, the activity of TiO2 modified with either platinum or nafion for H2 production was negligible under the same experimental conditions. The negatively charged nafion layer enhances the adsorption of cationic RhB and pulls protons, a source of hydrogen, to the surface of TiO2 through electrostatic attraction. On the other hand, platinum deposits on TiO2 can act as an electron sink and a temporary electron reservoir for the reduction of protons. With the production of H2, RhB was gradually degraded through N-deethylation, which was confirmed by the spectral blue shift of the maximum absorption wavelength (λmax) from 556 to 499 nm (corresponding to the λmax of rhodamine 110). With Pt/TiO2/Nf employed at [RhB]=20 μM (0.6 μmol), approximately 70 μmol of H2 was produced and RhB and its intermediates were completely removed over a 12 h period. A detailed reaction mechanism was discussed.